Senior Center Service Utilization: Do Social Ties Affect Participation Patterns?. (February 2022) - Keyes, Laura; Li, Qiwei; Collins, Brian; Rivera-Torres, Solymar
Purpose: A better understanding of service utilization patterns at senior service centers can improve program development and constituent usage Theory: This research examines whether participation in senior center activities is a function of senior socialization that reinforces and supports existing social ties by selecting specific activities in senior centers. Methods: A total of 924 participants of senior centers in a municipality in the Southwest were surveyed. Results: We find that having closer friends influences participation in certain senior center services. We also find that gender, race, ethnicity, and income also explain different usage rates beyond age. Conclusion: Opportunities to foster social interaction to grow and reduce barriers to participation and market to a broader range of current and potential participants are discussed.